Pregnant Women's Health Monitoring Application : Systematic Literature Review - Nugrahing Widi A.E; Runjati Runjati; Lanny Sunarjo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Maternal mortality remains a major challenge in Indonesia, particularly due to limited access to health services and low awareness of the importance of regular pregnancy check-ups. The use of information technology in the health sector, such as telemedicine, has shown great potential in improving health services, including for pregnant women. This study aims to examine applications for monitoring the health of pregnant women with chronic energy deficiency (CED), which can support medical personnel and pregnant women in monitoring health effectively. The research design is a Systematic Literature Review of articles or journals published in 2019-2024, accessed on Google Scholar, PubMed and Scopus with the Prisma Flow technique. This study found that telemedicine and digital health applications have great potential in improving access and quality of maternal health monitoring. The Android-based system allows for effective monitoring of nutritional status, vital signs, and communication between pregnant women and medical personnel. The use of digital technology-based health applications can be an effective solution to support monitoring the health of pregnant women so that it can help reduce maternal mortality rates (MMR) and infant mortality rates (IMR) in Indonesia through wider and more efficient access to health information.